Vestigialization of arsenic resistance phenotypes/genotypes in Chromobacterium violaceum strains thriving in pristine Brazilian sites. (October 2013) - Silva-Rocha, Rafael; de Azevedo, Juliana Simão Nina; Carepo, Marta S. P.; Lopes de Souza, Ricardo; Silva, Artur; de Lorenzo, Víctor; Schneider, Maria Paula Cruz
Abstract The performance of the arsenic resistance arsRCB operon of the ubiquitous bacterium Chromobacterium violaceum has been employed as a descriptor of the genomic persistence of traits for long-ceased environmental conditions. To this end, a reliable reference for arsenic resistance/sensitivity was created in the C. violaceum ATCC 12472-type strain by deleting its genomic ars operon. This allowed tracing all of the arsenic resistance of this bacterium to the ars gene cluster. A sample of 15 environmental C. violaceum strains isolated from pristine Amazonian sites (both rain forest and savannah) were then examined for the presence of arsRCB amplicons, for arsenic resistance, and for indications of decay of ars genes into pseudogenes. While the sites of origin of such strains have no record of industrial or geological exposure to arsenic, all of them bore the standard arsRCB cluster in their genome, but they did differ in their resistance to the metalloid. This ranged from complete sensitivity to tolerance levels above the reference C. violaceum ATCC12472. Inspection of relevant DNA sequences, phenotypic analyses and monitoring expression profiles of the ars genes in each strain exposed a distinct genetic drift of the system toward vestigialization, that is, accumulation of mutations leading to the loss of a non-used character. In particular, quantitative PCR revealed inducibility by arsenic to be the first trait to be lost in the route toward decaying and eventual nonfunctionalization. The data presented fit evolutionary predictions on elimination of non-used characters through a mere genetic drift accumulating neutral mutations.